2013
DOI: 10.1111/jcpe.12066
|View full text |Cite
|
Sign up to set email alerts
|

Osteotome sinus floor elevation with or without grafting: a 3‐year randomized controlled clinical trial

Abstract: Aims: To evaluate the clinical and radiographic results of dental implant placed using osteotome sinus floor elevation (OSFE) with and without simultaneous grafting. Materials & Methods: Forty-five patients were randomly assigned into two groups: Group1: OSFE with deproteinized bovine bone mineral (DBBM) mixed with autogenous bone chips, and Group2: OSFE without grafting. The endosinus bone gain (ESBG) was assessed on radiographs at 6, 12, 24, 36 months following surgery as primary outcome measurement. Implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
139
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(157 citation statements)
references
References 32 publications
15
139
1
2
Order By: Relevance
“…Three of the included trials reported on the endosinus bone gain . The test for heterogeneity showed no significant heterogeneity ( P = 0.40, I 2 = 0%).…”
Section: Resultsmentioning
confidence: 95%
“…Three of the included trials reported on the endosinus bone gain . The test for heterogeneity showed no significant heterogeneity ( P = 0.40, I 2 = 0%).…”
Section: Resultsmentioning
confidence: 95%
“…1,6 Two recent prospective randomized studies 7,8 have shown that grafted sinus floor elevation promotes more bone gain and better implantation than graft-free sinus floor elevation. However, there were no differences in clinical outcomes such as survival rates.…”
mentioning
confidence: 98%
“…11 In fact, the application of grafting material might provide no major advantage in clinical success. 12 Furthermore, the less invasive nature of OSFE has been found to provide increased case acceptance with decreased treatment time and expense. 13 Given the different possible sinus lift complications-including, but not limited to, perforation of the sinus membrane, obliteration of the sinus cavity, hemo-sinus, and sinusitis 14 -it is certainly desirable to develop suitable criteria for case selection.…”
mentioning
confidence: 99%